Ethnobiology of plants and animals used as ubarampe in the Kepungan tradition of the Javanese Community of Somongari, Purworejo District, Indonesia - FAJAR ADINUGRAHA; SITI ZUBAIDAH; SRI RAHAYU LESTARI; KAH HENG CHUA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Adinugraha F, Zubaidah S, Lestari SR, Chua KH. 2024. Ethnobiology of plants and animals used as ubarampe in the Kepungan tradition of the Javanese Community of Somongari, Purworejo District, Indonesia. Biodiversitas 25: 2521-2532. The Somongari Javanese community of Purworejo District, Central Java Province, Indonesia utilizes plants and animals as traditional ritual equipment, called ubarampe, which are offerings in the Kepungan tradition. The concept of ubarampe, comprising plants and animals, holds a distinct purpose and philosophical significance for the Somongari Javanese community. Unfortunately, knowledge about ubarampe in the Kepungan tradition has only been transmitted through oral and demonstration, and not yet been recorded in written and visual documentation, resulting in the younger generation being unaware of the use of plants and animals for ubarampe and their associated philosophical meanings. This study examines the ubarampe in the Kepungan tradition, including the types and their philosophical meanings as well as the plants and animals utilized. This study documented 19 types of ubarampe used by Somongari Javanese community in the Kepungan tradition, each of which utilizes plants and animals. Some plants and animals require cooking first, while others are directly used as ubarampe without cooking. The plant specimens utilized in ubarampe include eudicots (10 species), monocots (11 species), and magnoliids (1 species). The botanical components include leaves, flowers, seeds, fruits, bulbs, tubers, and rhizomes. Only one animal species from the Aves class was utilized for ubarampe. The utilization of species in ubarampe is the result of philosophical considerations of the ancestors of the Somongari Javanese community regarding the relationship between humans, nature, God, and ancestors. Consequently, the findings of this research are anticipated to facilitate an enhanced comprehension of plant and animal biodiversity as a valuable cultural legacy for present and future generations.